Export of dissolved and undissolved nutrients from forested catchments in Peninsular Malaysia - Yusop, Zulkifli; Douglas, Ian; Nik, Abdul Rahim (Elsevier BV, 2006)
Knowledge of rates of nutrient losses is crucial for sustaining the health of tropical forests. Investigations of dissolved and particulate nutrient export from two forested catchments (C1 and C2), at Bukit Tarek Experimental Catchment in Selangor, Malaysia revealed low levels of electrical conductivity and solute concentrations that reflect poor site fertility. Concentrations of K +, NO3-N and Mg2+ increased during storms whereas those of SiO2 and alkalinity decreased. Cumulative plots of monthly solute loadings exhibit three different patterns: (1) larger export during storms of NO3-N, K+, Mg2+ and Cl -; (2) larger export during low flow conditions of SiO2, PO43- and Na+; and (3) fairly equal export during low flow and storms for NH3-N and Ca2+. Such patterns demonstrate the roles of various flow paths for evacuating solutes. During heavy storms, near surface lateral flow takes up additional solutes from nutrient matter in the organic soil. SiO2 dominates the solute export in both catchments contributing about 76% of the total solute load. Compared to reported values for other tropical forest sites of varying fertility, exports of dissolved Ca2+ and K+ are low whereas Mg2+ is close to the average. However, when confined to sites with low soil fertility; the exports of Ca2+, Mg2+ and K+ at Bukit Tarek are similar to the medians of the reported values. Interestingly, export of Mg and Ca in suspended particulate matter (SPM) exceeded the removal of these nutrients in dissolved forms. This highlights the need to re-evaluate results of nutrient input-output budgets derived solely from dissolved loadings, especially when the net gains are small. Sources of stream litter were limited to near channel margins, resulting in very low outputs per unit area. Consequently, the nutrient losses via this mode were negligible compared to the dissolved load. Removal of nutrients in bed load was also small, being less than 1% of the dissolved loads except for N (2.1 and 2.5% for C1 and C2, respectively) and total P (7.5 and 11%, respectively).